1990
DOI: 10.1105/tpc.2.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regulatory elements involved in the induction of two tobacco genes by salicylate treatment and virus infection.

Abstract: Tobacco genes encoding the PR-la protein and a glycine-rich protein are expressed after treatment of plants with salicylate or infection with tobacco mosaic virus. Upstream sequences of these genes were fused to reporter genes, and these constructs were used to transform tobacco. Upstream sequences of the PR-la gene of 689 base pairs or longer were sufficient for induction of the reporter gene in tobacco mosaic virus-inoculated leaves, systemically induced leaves from infected plants, and leaves treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
35
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 23 publications
9
35
2
Order By: Relevance
“…-643 and -689, which further supports the idea that SA is an endogenous signal for the plant defense (27). It was shown that unencapsidated viral RNA, not coat protein, elicited SA accumulation and that the SA level was proportional to TMV concentration (29).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…-643 and -689, which further supports the idea that SA is an endogenous signal for the plant defense (27). It was shown that unencapsidated viral RNA, not coat protein, elicited SA accumulation and that the SA level was proportional to TMV concentration (29).…”
supporting
confidence: 66%
“…Among several molecules that have been proposed as endogenous signals for the defense response to pathogens (3,4,25,30), SA2 was recognized as a key molecule that triggers local and systemic responses of tobacco to viral infection (14,15,19,27,29). SA levels in resistant, but not in susceptible, tobacco increase drastically in both TMVinfected and uninfected leaves in the same plant (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By functional analyses in transgenic tobacco plants, we show, as has been reported by Van de Rhee et al (1990), Van de Rhee and Bol(l993) and Uknes et al (1993), that 906 bp of the PR-1 a 5'-flanking region are sufficient to obtain reporter gene expression in young plants in response to TMV infection in the course of the hypersensitive reaction and to treatment of the plants with AcSiaCOOH. Furthermore, we demonstrate that this region of the PR-1 a gene also mediates reporter gene expression in older plants during the normal development of the tobacco plant.…”
Section: Discussionmentioning
confidence: 57%
“…Transgenic tobacco plants were generated with these constructs and monitored for reporter gene expression in the context of the hypersensitive defense reaction and after treatment of the plants with (Ac)SiaCOOH. By this analysis, it has been concluded that positive cis-acting elements must be located 5' from position -335 in the PR-1 a sequence (Beilmann et a]., 1991,1992), and more precisely at positions -689 to -600 ( Van de Rhee et al, 1990; Van de Rhee and Bol, 1993;Uknes et al, 1993). Other results have also been reported claiming that 0.3 kb of the PR-1 a 5'-flanking region are sufficient for a regulated expression of PR-1 genes (Ohshima et al, 1990~).…”
mentioning
confidence: 99%